Ciclo económico de Colombia: una mirada desde la teoría austriaca (1994-2004) (2007)
The Austrian Business Cycle Theory is founded on monetary transmission mechanisms in order to explain peaks and troughs in the business cycle. According to Austrian postulates, markets are dynamic interaction processes among economic agents, in which a general situation of coordination between consumption and production plans through time is not identifie . Asymmetric information is deemed to be the cause of such impossibility. Thus, the economic system fluctuates according to two tendencies: disequilibrium, caused by the absence of complete information, and equilibrium, based on the agent’s innate sense of generating opportunities for economic benefits. Based on these ideas, the existing relationship between real and monetary variables in the Colombian economy between 1990 and 2005 is analyzed. This is done though a graphical analysis and a through a model of co-integration.